The Synchronous Online Argumentation System User Interface with an Integrated Design Framework: Redesign and Evaluation - Nuswantari, Ayu; Wu, Ying-Tien; Surjono, Herman Dwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
The Synchronous online argumentation system is highly needed to facilitate learning activity in this internet era. To gain deeper insights about this important issue, this study developed nine principles based on Cognitive Load, User Interface, and User Experience to redesign a system. With this framework, 48 (forty-eight) students of Chi-Ying High School had tested with two prototypes, and the second prototype used the nine principles. The systems were measured with Web-Based Learning Environment (WEBLEI) and System Usability Test (SUS). The result of WEBLEI measurement shows that the second prototype gives better result and shows higher user acceptance than the first prototype. The result of SUS measurement shows that the usability of the second prototype is better than on the first prototype with (4.43) SUS score difference. The result shows that the use of nine principles that applied to the second prototype does increase the usability and acceptance of the students.